Students’ Perception of Online Model United Nations in Improving EFL Students’ Speaking Ability - Aisyah, Putri Nur (Indonesian Journal of English Language Studies (IJELS), 2022)
Model United Nations (MUN) is a formal activity for youth to have a simulation of the United Nations assembling. This activity requires formal and academic language proficiency, predominantly in English. MUN is quite typical for debate competitions. Nevertheless, since the terms of the pandemic, there have been several setting changes to MUN’s procedure. MUN has been chiefly held in a virtual environment. Furthermore, this research is established to explore students' perception of the new online setting of MUN for their speaking ability. This research is phenomenological descriptive qualitative where it explored participants' perspectives in online MUN events. The data was taken with purposive sampling to collect participants with several experiences in online MUN events. Moreover, interviews will be implemented as a data collection method. It reveals most students infer that MUN allows them to gain confidence and fluency development in speaking components. On the other hand, it also provides a positive impact on their academic performance.